Regulatory competition and international cooperation - Philipp Genschel; Thomas Plümper (Max Planck Institute for the Study of Societies, 1997)
Recent research has shown that regulatory competition does not necessarily lead to downward pressures on regulation, but may at times also push the level of regulation upwards. Extending David Vogel's California effect argument, this paper shows that such upward pressure may not only result directly from the dynamics of the competitive process but also from international cooperation. Evidence from two case studies on international capital market regulation is used to identify the conditions under which cooperation in the shadow of regulatory competition is likely to succeed or fail. The successful multilateral standardisation of banking capital requirements in the BIS is compared to failed attempts to harmonise interest taxation across EC member states.
Keywords: 300